Assessment of the effects of the use of preconsumer cotton waste on the quality of rotor yarns - Krupincová, Gabriela (Heliyon, 2024)
Due to the shortage of raw fiber materials and stricter legislative conditions, it has become necessary to process even the more contaminated fiber wastes that contain only a small amount of useable fibers. Hence, this paper investigates the impact of different cleaning channels on the Rieter R37 rotor spinning machine in controlling spinning strategy and yarn quality using recovered blowroom cotton waste fibers. The study involves spinning 98-tex yarns with different cleaning channels during the spinning process, using recovered blowroom cotton waste in blends with virgin cotton processed into slivers by two methods. Qualitative indicators in the fiber-sliver-yarn line were evaluated and graphically compared. The statistical significance of the influencing factors was determined using the Generalized Anova. Additionally, the quality of the experimental samples was compared to authentic data from global production using the USTER® STATISTIC. The results underline the significant influence of fiber quality, sliver preparation method and implemented cleaning channels on the arrangement of fibers in yarn structures as evidenced by structural and mechanical parameters. In particular, the comparison with USTER® STATISTICS confirms that all yarns meet the required quality standards for selected applications, including those spun exclusively from 100 % cotton waste. Furthermore, the results demonstrate that this innovative technology enables yarn manufacturers to meet customer demands, ensure optimal yarn quality and achieve cost savings by optimizing waste removal without compromising fiber yield.
Keywords: Rotor cotton spun yarn; Yarn quality; Trash count and dust count; Trash and dust; Cotton waste